KINERJA PENDIDIKAN MENENGAH DI INDONESIA DALAM MENINGKATKAN MUTU PENDIDIKAN - Sri Winarsih (Jurnal Kependidikan)
Education is an "investment". Education is the process of forming the basis of the fundamental capabilities, both related to cognitive (intellectual) and emotional power (feeling), which is directed to human nature and to each other. Problems of teachers in secondary education in Indonesia are as follows. (1) Lack of teachers: deployment of teachers in Indonesia is not in accordance with the needs in each educational unit; there is a tendency surplus of teachers in certain areas, while other areas (outside Java) are lack of teachers. (2) The qualifications of teachers: many teachers have not their minimal education qualifications (S1 degree). (3) Academic competence and qualifications: the results of the competency test conducted on random teachers in 2004 are not satisfactory. (4) Unsuitable education background: Many teachers teach subjects that are not in accordance with their educational background. In order that the planning formulated at the national level is supported and implemented in the education ranks below, it is recommended to implement an optimal management, "Planning Philosophy", as depicted in the "Sustainable development planning pentagon" in this article.